TEACHER WRITTEN-CORRECTIVE FEEDBACK: A CASE STUDY IN EFL WRITING CLASSROOM - Dyah Fitri Mulati; Faricha Rizqi; Eka Pratiwi Yunianti; Arif Alexander Bastian; Defy Gustianing; Septika Ariyanti (IKIP Siliwangi, 2023)
Feedback is commonly implemented as the scaffolding learning technique in second and foreign language writing. The importance of this has also been acknowledged as a way for students to manage their writing abilities better, which is a crucial component of the process-based learning environment. However, the published literature on secondary teachers' responses to students' writing in an EFL context is less extensive. Furthermore, limited is known about the causes of the current feedback practices and the reasons behind the teacher’s reactions to student writing. As a result, this study, which includes a teacher as a participant, investigates the application of written-corrective feedback in secondary school. This study was a case study aimed at (1) examining written-corrective feedback practice the teacher provides and (2) outlining the factors that influence teacher's practices of giving written-corrective feedback. The data were garnered by a document analysis and interviews adapted from Lee (2009) comprising five items associated with the practices in implementing written-corrective feedback type and strategy, respected by variables that form those practices. The results demonstrated that teachers preferred to use uncoded, indirect, hints, and selective written-corrective feedback. Additionally, it was discovered that those practices were primarily affected by personal experience and improvement in her practice. Keywords: Written-Corrective Feedback; Practices; Factors; EFL Context